2021
DOI: 10.1093/eurheartj/ehab121
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic noise and cardiovascular disease risk factors in UK Biobank

Abstract: Aims The aim of this study was to investigate the cross-sectional associations of modelled residential road traffic noise with cardiovascular disease risk factors [systolic (SBP) and diastolic blood pressure (DBP), C-reactive protein, triglycerides, glycated haemoglobin, and self-reported hypertension] in UK Biobank. Methods and results The UK Biobank recruited 502 651 individuals aged 40–69 years across the UK during 2006–10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 43 publications
2
43
0
2
Order By: Relevance
“…Intriguingly, in our experiment, the changes in inflammatory cytokine levels in heart samples in noise exposure and noise insulation environments were much more notable than those in sympathetic ganglia, which indicate the existence of other potential proinflammatory mechanisms apart from the neuroendocrine-cardiovascular axis. Recently, data from the UK Biobank revealed a more complicated association between noise and cardiovascular risk [ 54 ]. Glycated hemoglobin levels, blood pressure, body mass index, C-reactive protein levels, and triglyceride levels are relatively higher in people living in an environment of ≥65 Db than in people living in an environment of ≤55 dB, and this effect was not affected by the use of relevant medications.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, in our experiment, the changes in inflammatory cytokine levels in heart samples in noise exposure and noise insulation environments were much more notable than those in sympathetic ganglia, which indicate the existence of other potential proinflammatory mechanisms apart from the neuroendocrine-cardiovascular axis. Recently, data from the UK Biobank revealed a more complicated association between noise and cardiovascular risk [ 54 ]. Glycated hemoglobin levels, blood pressure, body mass index, C-reactive protein levels, and triglyceride levels are relatively higher in people living in an environment of ≥65 Db than in people living in an environment of ≤55 dB, and this effect was not affected by the use of relevant medications.…”
Section: Discussionmentioning
confidence: 99%
“…The associations of CVDs with avoidable exposures, other than those due to behaviors such as tobacco smoke or alcohol consumption, are well established for many categories of toxic by-products from human activities (e.g., traffic, industries, waste disposal, energy production from fossil fuels) [ 8 ] and manufactured products as Persistent Organic Pollutants (POPs) which accumulate in the environment [ 9 ]. However, the increasing incidence and prevalence of cardiovascular diseases (CVDs) has attracted researchers’ interest in providing new evidence on the direct effects of the physical–chemical environment on myocardial damage.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that noise sensitivity, rather than the noise level, predicts the non-auditory health hazards of noise (14). However, almost all these studies adopted model estimated road traffic noise in the analysis, which may be inaccurate as the layout of rooms in the house, window opening habits, and indoor noise levels were not taken into account (15), indeed, noise sensitivity was also not considered. Also, most of these findings come from Europe and North American countries.…”
Section: Introductionmentioning
confidence: 99%